Translator’s Strategies in Delivering The Content of Novel Entitled The Old Man and the Sea Written by Ernest Hemingway - aji septiaji (English Language Education Department, Universitas Majalengka, 2024)
Various methods of translation support a writer in mastering the structure, form, and meaning that exist in variety works both in printed (text) and electronic (online). In translating a sentence, a writer can use several methods. The use of a method can affect the meaning of the source language. Through translation, the readers in general can distinguish texts between the original and translated texts, understand the origin of the works in the source language, for example, the work of Indonesian language which translated from English, or vice versa. The existing translation methods are divided into seven categories namely, borrowing, calque; literal; transposition / shifted; modulation; equivalent; and adaptation. The result of this research shows that there are three methods which used by the author in translating the novel written by Ernest Hemingway entitled The Old Man and the Sea which is transtlated into Lelaki Tua dan Laut. The methods are literal, equivalent, and borrowing.